ALLOCATION OF GENERATION PLANTS THAT GIVES MINIMUM LOSSES FOR IRAQI SUPER GRID NETWORK - Afanin A. Abood; Samir S. Mustafa (Journal of Engineering, 2009)
The main goal of this work is to determine optimal location for placing generating plants in the Iraqi National Super Grid which gives minimum total losses in the system. A package build under Matlab was used to allocate optimal placement of generating sets, calculating active and reactive power for these generators, .calculating system minimum losses, and determine the effect of varying the output of the generators used on losses reduction.